Do Audit Tenure and Audit Committee Gender Diversity Affect Audit Report Lag? A Study on Energy Firms in Indonesia - Naila Zahra Nurrahmi; Wawan Setiawan; Erna Fitri Komariyah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines how audit tenure and gender diversity on the audit committee influence audit report lag (ARL). It focuses on energy sector firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The ARL measures the timeliness and accuracy of reports, essential for stakeholder interests. Longer audit tenures may increase audit efficiency, and increased gender diversity in the audit committee could enhance oversight and governance. The study employs a panel data approach and multiple linear regression analysis. The sample consists of 43 energy sector companies selected through purposive sampling, meeting the research criteria. Results indicate that longer audit tenure significantly reduces ARL, while gender diversity in the committee also has a notable effect. It highlights the importance of proper auditor rotation and increasing women's representation in audit committees to enhance the audit reporting process.